Excised DNA circles from V(D)J recombination promote relapsed leukaemia - Zeqian Gao; James N. F. Scott; Matthew P. Edwards; Dylan Casey; Xiaoling Wang; Andrew D. Gillen; Sarra Ryan; Lisa J. Russell; Anthony V. Moorman; Ruth de Tute; Catherine Cargo; Anthony M. Ford; et al. (Nature, 2025)
Abstract Extrachromosomal DNA amplification is associated with poor cancer prognoses1. Large numbers of excised signal circles (ESCs) are produced as by-products of antigen receptor rearrangement during V(D)J recombination2,3. However, current dogma states that ESCs are progressively lost through cell division4. Here we show that ESCs replicate and persist through many cell generations and share many properties in common with circular extrachromosomal DNAs. Increased ESC copy numbers at diagnosis of B cell precursor acute lymphoblastic leukaemia were highly correlated with subsequent relapse. By taking advantage of the matching recombination footprint that is formed upon the generation of each ESC, we measured ESC persistence and replication and found increased ESC replication in patients who later relapsed. This increased replication is controlled by cell-intrinsic factors and corresponds to increased expression of DNA replication- and repair-associated genes. Consistent with high ESC levels having a role in disease progression, the number of mutations typical of those caused by the V(D)J recombinase–ESC complex was significantly increased at diagnosis in patients who later relapsed. The number of such mutations in genes associated with relapse increased between diagnosis and relapse, and corresponded to clonal expansion of cells with high ESC copy numbers. These data demonstrate that the by-product of V(D)J recombination, when increased in abundance, potently associates with the V(D)J recombinase to cause adverse disease outcomes.